A Force for Democracy? Representations of the US Government in American Coverage of Venezuela - MacLeod, Alan (Frontiers in Communication, 2019)
Abstract: Since the election of Hugo Chavez the United States has played a highly questionable role interfering in Venezuelan politics, funding, training and supporting attempts at coups to remove democratically elected presidents. Yet the American media (The New York Times, Washington Post and Miami Herald) have presented the US overwhelmingly positively, portraying it as a force for democracy and stability in the region, contrary to the wealth of official evidence. This content and discourse analysis study focuses on the coverage of four key events in recent Venezuelan history and concludes that the concept of “democracy” in the media is automatically applied to official US policy, whatever it happens to be. Thus, the official American ideology of its fundamental benevolence and exceptionalism is not disputed, even when circumstances clearly challenge this concept.